Rancang Bangun Mesin Pengering Maggot Tipe Rotary Dryer Menggunakan Pemanas Infrared Burner dengan Metode NIDA Guna Memproduksi Maggot Kering - Kuswandi, M Rayhan; Ramadhan, Safarudin (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Organic waste management is a crucial issue in urban areas such as Semarang City, especially in terms of efficiency and environmental impact. REPRO MSME as an organic waste processing player has utilized Black Soldier Fly (BSF) larvae or maggot as an environmentally friendly bioconversion agent with high nutritional value. To increase added value, maggot is developed into dry products through the drying process. However, the rotary dryer machine used today is inefficient because it does not match the daily production capacity of fresh maggot of 30-40 kg. This study aims to design an energy-efficient maggot drying machine and according to production capacity using the NIDA (Need, Idea, Decision, Action) method. The results of the research design that has been carried out using the NIDA method, Alternative 2 was chosen to be the maggot dryer design with a score of 390.57, obtained a maggot dryer system with an infrared burner heater in the tube. From testing the maggot drying machine, the test results of 5 kg of maggot obtained a time of 64 minutes with optimal drying results.